Carboxy methyl and carboxy analogs argaminolics B and C - Klika, Karel D.; Khallouki, Farid; Owen, Robert (Records of natural products, 2015)
Two new analogs, a carboxy methyl (Argaminolic B) and a carboxy derivative (Argaminolic C), of a recently reported amino phenolic, Argaminolic A, isolated from the fruit of the argan tree, Argania spinosa(Skeels L.), are described. Argaminolic B exhibits facile hydrolysis of its methyl ester to yield Argaminolic C, which then undergoes a remarkably facile decarboxylation to the previously described Argaminolic A.